PENERAPAN RECIPROCAL TEACHING DENGAN KARTU PERAN UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS MATERI TRIGONOMETRI - Puspitasari, Elisa Dewi (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2020)
The purpose of this study is to describe the application of Reciprocal Teaching with role cards to improve student mathematical reasoning abilities on trigonometry material. Mathematical reasoning is thinking about mathematical problems logically to solve a problem and give reasons for a solution. One of the lessons learned to overcome the low mathematical reasoning ability is the learning of Reciprocal Teaching models using role cards. The steps of Reciprocal Teaching activities include question generating, clarifying, predicting, and summarizing. Before the Reciprocal Teaching steps are carried out, students are given a role card to determine the students who become model teachers. This research is a classroom action research. Based on the research that has been done, it is known that the application of the Reciprocal Teaching model increases the mathematical reasoning ability of students in XI grade IPA 2 of SMA Negeri 8 Malang on the Trigonometry with an increase in class average from initial 73 to 60 in cycle I and to 73 in cycle II. In addition, the average percentage increase in students' mathematical reasoning also increased from 60% to 73%.